2002
DOI: 10.1080/00380237.2002.10570694
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Political Constraints in the Gulf War Illness Social Movement

Abstract: Recent contributions to social movement theory have emphasized the importance of cultural and political opportunities in shaping movement growth and development. While most ofthat work focuses on how these factors facilitate social movement efforts, we examine a case in which cultural and political factors have constrained the efforts of a social movement. Analyzing data from in-depth interviews with 55 respondents, we examine the organizing efforts of Gulf War veteran* claiming illnesses connected to environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Brown [26] and Shriver [27,28] have contributed extensive research into the social discovery of Gulf War-related illness and associated controversies over veterans’ environmental exposures. This scholarship has revealed the complex entanglements between EH issues and military practices and technologies and builds on prior accounts of military contamination such as Vietnam veterans’ suffering the health consequences of Agent Orange and “atomic veterans” exposed to radiation.…”
Section: Social Science Studies Of Environmental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Brown [26] and Shriver [27,28] have contributed extensive research into the social discovery of Gulf War-related illness and associated controversies over veterans’ environmental exposures. This scholarship has revealed the complex entanglements between EH issues and military practices and technologies and builds on prior accounts of military contamination such as Vietnam veterans’ suffering the health consequences of Agent Orange and “atomic veterans” exposed to radiation.…”
Section: Social Science Studies Of Environmental Healthmentioning
confidence: 99%
“…They find that Gulf War veterans’ illness claims were undermined by incomplete data, scientific uncertainty, multiple exposures, and political controversy [26]. Similarly, Shriver and colleagues investigate Gulf War veteran efforts to construct and legitimize an environmental illness frame, along with the U.S. government’s subsequent refusal to recognize that frame despite complaints from over 100,000 individuals [27,28]. Against the backdrop of current and future 21st-century U.S. militarism, such analyses have enduring relevance to human and environmental health.…”
Section: Social Science Studies Of Environmental Healthmentioning
confidence: 99%
“…Prior to and during the First World War the grading of recruits into categories "was based as much on perceptions of the relationship between physical masculinity and combativeness as it was on medical principles of healthiness" (Bourke 1999: 109). Shriver et al (2002a) have suggested that there were a number of cultural constraints to US veterans labelling their illness as GWS: their continuing patriotism, their value of group cohesion and an idealisation of strength and vigour. The latter was related to the association of military pursuits and health with masculinity.…”
Section: Morgan Writesmentioning
confidence: 99%
“…Such ongoing loyalty to the forces has been seen in the US as one major constraint for veterans in thinking of their illness as GWS (Shriver et al 2002a). The veterans interviewed by these authors remained very patriotic, which "often led to difficulty connecting their sickness to their wartime experience as they had to reconcile their patriotism with their belief that the government is not acting appropriately" (ibid.…”
Section: Leaving the Militarymentioning
confidence: 99%